Peran Penulis Naskah Dalam Pembuatan Program Feature Kuliner “Rasa Nusantara” Edisi Warung Mjs - Annisa Cikal Kartika Putri Madya; Muhammad Darwinsyah (Lembaga Pengembangan Kinerja Dosen, 2024)
Abstract - Indonesia can be said to be a place rich in culinary delights because there are various types of cuisine in each region, both in the form of heavy meals and snacks. The progress of increasingly modern times has more or less influenced the decline in the popularity of several typical Indonesian foods. Television must develop more creativity in Indonesian culinary feature programs. Therefore, a culinary feature program entitled